Correction: automated and controlled mechanical stimulation and functional imaging in vivo in C. elegans. Issue 22 (24th October 2017) - Cho, Yongmin; Porto, Daniel A.; Hwang, Hyundoo; Grundy, Laura J.; Schafer, William R.; Lu, Hang
Abstract : Correction for 'Automated and controlled mechanical stimulation and functional imaging in vivo in C. elegans ' by Yongmin Cho et al., Lab Chip, 2017, 17, 2609–2618.